Euglena gracilis Promotes Lactobacillus Growth and Antioxidants Accumulation as a Potential Next-Generation Prebiotic - Dai, Junjie; He, Jiayi; Chen, Zixi; Qin, Huan; Du, Ming; Lei, Anping; Zhao, Liqing; Wang, Jiangxin (Frontiers in Nutrition, 2022)
Euglena gracilis, a unicellular microalga with both autotrophic and heterotrophic growth styles under different cultivation conditions, contains many nutrients such as beta-1,3-glucans, 20 essential amino acids, fatty acids, vitamins, and minerals and has recently attracted attention as a new health food. Among them, beta-1,3-glucans, paramylon of Euglena, is an insoluble dietary fiber and is well known as an immune booster, attenuator of obesity and diabetes, reducer of acute liver injury, and suppressor of atopic dermatitis and other chronic inflammatory disorders. Recently, evidence has appeared for the positive health effects of foods, food ingredients or biochemical compounds derived from several other microalgae, such as Chlorella, Spirulina, Dunaliella, Phaeodactylum, and Pavlova. Until most recently, prebiotic activity of Euglena and paramylon was reported. Emerging prospects of microalgae as prebiotic were well summarized but the mechanisms behind the bacterial growth promotion by microalgae are not elucidated yet. Thus we evaluated and compared prebiotic prospects of both autotrophically and heterotrophically grown Euglena on 6 different strains of Lactobacillus. What’s more, the stimulated mechanism was revealed by bacterial culture medium metabolomic analysis. This study could widen the knowledge about prebiotic activity of Euglena and other microalgae derived compounds as potential health foods.